Laser chemical vapor deposition of Lu2O3:Eu scintillation film. (24th May 2019) - Chang, Jingyu; Qi, Yunhang; Zhao, Hengyu; Mao, Rihua; Chen, Bangrui; Feng, He; Xu, Zhan; Zhang, Zhijun; Zhao, Jingtai
Abstract: Lu2 O3 :Eu scintillation film is one of the most attractive candidate for the hard x-ray imaging, especially above 20 keV. A micro-columnar film with 10 μ m thickness of Lu2 O3 :Eu was firstly obtained by laser chemical vapor deposition on not-oriented Lu2 O3 single crystal substrate. The morphology of obtained film was investigated by the scanning electron microscopy. The photoluminescence and scintillation properties were measured and discussed, including photoluminescence excitation and photoluminescence curves, photoluminescence decay curves, and x-ray excited luminescence curve.